1995
DOI: 10.1079/bjn19950048
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of activity of hydrolytic enzymes in the digestive tract of rabbits

Abstract: Activities of twelve hydrolytic enzymes in the digestive tract of young rabbits before weaning (4 weeks old) and adult rabbits (3 months old) were measured. The principal digestive enzymes in both groups of rabbits appeared to be amylase (EC 3.2.1. l), maltase (EC 3.2.1.20), pectinase (EC 3.2.1.15) and proteinases. The stomach of young rabbits contained most of the lipolytic activity and 45.7 YO of the total proteolytic activity of the digestive tract. The highest specific activities (per g digesta) of amylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
1
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 18 publications
8
54
1
5
Order By: Relevance
“…Our results showed that availability of pancreatic amylase and lipase for substrates in the small intestine increased with age, which is in agreement with the age increase of their activities previously described in the pancreas Dojanȃ et al, 1998;Debray et al, 2003). The increase in amylase activity probably results from the higher starch intake with age (Marounek et al, 1995;Scapinello et al, 1999), and should correspond to an increasing capability of rabbits to digest starch. Conversely, in our study, the increasing lipase activity with age was not parallel to crude fat intake, which sharply decreased at weaning (from milk having 9% to 16% lipids to solid vegetal feed with 3% to 5% lipids).…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that availability of pancreatic amylase and lipase for substrates in the small intestine increased with age, which is in agreement with the age increase of their activities previously described in the pancreas Dojanȃ et al, 1998;Debray et al, 2003). The increase in amylase activity probably results from the higher starch intake with age (Marounek et al, 1995;Scapinello et al, 1999), and should correspond to an increasing capability of rabbits to digest starch. Conversely, in our study, the increasing lipase activity with age was not parallel to crude fat intake, which sharply decreased at weaning (from milk having 9% to 16% lipids to solid vegetal feed with 3% to 5% lipids).…”
Section: Discussionsupporting
confidence: 91%
“…Greater enzymatic activity for degrading pectins and hemicelluloses than for degrading cellulose has been detected in the rabbit caecal ecosystem (Marounek et al, 1995;Jehl and Gidenne, 1996). Accordingly, the digestion of hemicelluloses is higher than that of cellulose (Table 3), and smaller counts of cellulolytic bacteria were found in the rabbit caecum compared with xylanolytic or pectinolytic bacteria (Boulahrouf et al, 1991).…”
Section: Brief Overview Of Polymers Of the Plant Cell Wall: Definitiomentioning
confidence: 99%
“…Kits begin to consume limited amounts of solid feed at 18 to 20 days of age (Maertens and de Groote, 1990;Scapinello et al, 1999), then the microflora begins caecal colonization and fermentation develops soon afterwards (Gidenne, 1997), and some of the enzymatic digestive activities show important changes (Marounek et al, 1995). Early weaning reduces the incidence of digestive disorders and reduces pathogen transmission by limiting contacts between litters and does (Schlolaut, 1988).…”
mentioning
confidence: 99%